(untitled) (Bangladesh Journal of Otorhinolaryngology, 2012)
Ramsay Hunt Syndrome classically presents with VII nerve palsy. Other cranial nerve involvement is rare. We describe a case here who presented with VII, IX and X cranial nerve palsies and review the literature. DOI: http://dx.doi.org/10.3329/bjo.v18i2.12029 Bangladesh J Otorhinolaryngol 2012; 18(2): 231-233